X‐ray diffraction with micrometre spatial resolution for highly absorbing samples. (5th October 2022) - Chakrabarti, Prerana; Wildeis, Anna; Hartmann, Markus; Brandt, Robert; Döhrmann, Ralph; Fevola, Giovanni; Ossig, Christina; Stuckelberger, Michael Elias; Garrevoet, Jan; Falch, Ken Vidar; Galbierz, Vanessa; Falkenberg, Gerald; et al.
Abstract : A demonstration of high‐resolution micro X‐ray diffraction at high photon energies for highly absorbing samples. Abstract : X‐ray diffraction with high spatial resolution is commonly used to characterize (poly)crystalline samples with, for example, respect to local strain, residual stress, grain boundaries and texture. However, the investigation of highly absorbing samples or the simultaneous assessment of high‐ Z materials by X‐ray fluorescence have been limited due to the utilization of low photon energies. Here, a goniometer‐based setup implemented at the P06 beamline of PETRA III that allows for micrometre spatial resolution with a photon energy of 35 keV and above is reported. A highly focused beam was achieved by using compound refractive lenses, and high‐precision sample manipulation was enabled by a goniometer that allows up to 5D scans (three rotations and two translations). As experimental examples, the determination of local strain variations in martensitic steel samples with micrometre spatial resolution, as well as the simultaneous elemental distribution for high‐ Z materials in a thin‐film solar cell, are demonstrated. The proposed approach allows users from the materials‐science community to determine micro‐structural properties even in highly absorbing samples.